A Systems Study on Arms Corporation of the Philippines Materials Management Division Finished Goods Warehouse - Abuel, Alfonso; Cruz, Ramona H.; Ildefonso, Cristine R.; Uy, Veronica C.; Vytiaco, Donato R. (College of Engineering, 1988)
Arms Corporation of the Philippines started when two men, Squires and Bingham, invested on a print shop in 1905. The company, which was christened Squires-Bingham later dealt with motorcycles and other related merchandise. Only in 1941 did it expand to include the importation of firearms and ammunition. The decision to manufacture these products came about only after the war in 1945, when interest in game and sport flourished. Machines were brought and a system for machining and assembly was established. Today, firearms and ammunition manufactured by the Arms Corporation of the Philippines are faring very well in domestic and export markets. The firearms line includes rifles, shotguns, and revolvers; while the better selling ammunition are .22 LR, .22 Magnum, 9 mm, .357, 5.56 Ball or .223. and .38 caliber cartridges. The export market keeps the company's plant in Parang, Marikina in continuous operation. This is because the volumes are such that it would take around eight months to complete these export orders. The orders are placed during a Shot Show, held in the United States, where buyers and sellers of arms-related products meet. Competition in the export market is intense, unlike in the local market where the company is virtual monopoly. It follows that the company's pricing policy must be competitive in the former, but it can dictate its prices in the latter, for obvious reasons. This is why the company places local orders on top of its priority list. Simply stated, it makes more profit from its local sales than its export sales per unit of product sold. The export sales, however, make up for this by its sheer volume. The company is currently enjoying a modest profit from its operations. If this trend of concern the company is showing over improving its productivity continues, it is not unusual that it becomes one of the largest arm manufacturers not only of Southeast Asia but of the world.